Behind the numbers: Exploring caste inequities in entrepreneurial success - Rajesh S. N. Raj; Kunal Sen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
The documented under-representation of marginalized groups in business ownership and the labour market is a concerning issue. This study explores how caste disparities in small-firm entrepreneurship impact on firm performance in India, focusing on the informal sector. Our examination shows a significant productivity gap between firms owned by disadvantaged castes and others, including Other Backward Classes and Forward Castes, across the productivity distribution. The results of our decomposition exercise provide evidence for the importance of both differences in observables and returns to these observables in explaining the caste gap in productivity. This implies that even with improvements in firm attributes for Scheduled Caste or Scheduled Tribe businesses, the productivity disadvantage of firms owned by marginalized groups may persist. Pervasive market and non-market discrimination against marginalized groups suggests that the significant caste disparities in entrepreneurship and business performance will continue to impede the economy, presenting serious challenges for public policy.
Keywords: J16; L25; L26; L60; 330; caste; productivity gap; informal-sector firms; discrimination; India